Endurance performance in Basketball: comparison by age categories - Cengizel, E.; Dölek, B. E.; Suveren-Erdoðan, C.; Cengizel, C. Ö. (Acta Kinesiologica, 2022)
The aim of this study was to investigate the endurance performance in the male basketball players according to age categories. Totally 89 male healthy basketball players (age between 10-16 years) were voluntarily participated in this study. The age categories are determined as under 12 age (U12) novice, under 14 age (U14) little, under 16 age (U16) youth and under 18 age (U18) junior. 20 m shuttle-run test applied to determine the endurance performances of the subjects. VO2max, number of laps and total distance parameters are examined. It has been found that endurance performance increases with age. However, this increase was determined to be significantly different between the age categories (p<0.05). Although it was determined that endurance performance increased with age in male basketball athletes, there is no significant difference in endurance performance between U12 and U14. It is recommended to examine the lack of difference between novice and little teams in terms of adolescence and/or transition to adolescence.